Berlin the downfall, 1945 - Beevor, Antony (Penguin Books, 2003)
The Storming of Berlin had been the Red Army's dream of vengeance ever since the German's invasion of Russia in the summer of 1941. This book reconstitutes the experience of those millions caught up in the nightmare crescendo of the Third Reich's final defeat.